The Maternal-Effect Gene cellular island Encodes Aurora B Kinase and Is Essential for Furrow Formation in the Early Zebrafish Embryo - Yabe, Taijiro (Public Library of Science, 2009)
Females homozygous for a mutation in cellular island (cei) produce embryos with defects in cytokinesis during early development. Analysis of the cytoskeletal events associated with furrow formation reveal that these defects include a general delay in furrow initiation as well as a complete failure to form furrow-associated structures in distal regions of the blastodisc. A linkage mapping-based candidate gene approach, including transgenic rescue, shows that cei encodes the zebrafish Aurora B kinase homologue. Genetic complementation analysis between the cei mutation and aurB zygotic lethal mutations corroborate gene assignment and reveal a complex nature of the maternal-effect cei allele, which appears to preferentially affect a function important for cytokinesis in the early blastomeres. Surprisingly, in cei mutant embryos a short yet otherwise normal furrow forms in the center of the blastodisc. Furrow formation is absent throughout the width of the blastodisc in cei mutant embryos additionally mutant for futile cycle, which lack a spindle apparatus, showing that the residual furrow signal present in cei mutants is derived from the mitotic spindle. Our analysis suggests that partially redundant signals derived from the spindle and astral apparatus mediate furrow formation in medial and distal regions of the early embryonic blastomeres, respectively, possibly as a spatial specialization to achieve furrow formation in these large cells. In addition, our data also suggest a role for Cei/AurB function in the reorganization of the furrow-associated microtubules in both early cleavage- and somite-stage embryos. In accordance with the requirement for cei/aurB in furrow induction in the early cleavage embryo, germ plasm recruitment to the forming furrow is also affected in embryos lacking normal cei/aurB function.